A European survey of bowel preparation in colorectal surgery. (1st November 2017) - Devane, L. A.; Proud, D.; O'Connell, P. R.; Panis, Y.
Abstract: Aim: Meta‐analysis has shown that mechanical bowel preparation (MBP) does not improve outcomes in colonic surgery; however, there is uncertainty regarding MBP use in laparoscopic and rectal surgery and the addition of oral antibiotic regimens. The aim of this study was to assess current use of bowel preparation among European surgeons. Method: An online survey was circulated to members of the European Society of Coloproctology. Chi‐squared analysis was used to compare subgroups. Results: A total of 426 surgeons responded to the survey. MBP is routinely prescribed by 29.6% of respondents prior to colonic surgery and in 77.0% prior to rectal surgery. In the cohort performing > 30% of colorectal operations laparoscopically ( n = 294), routine use of MBP in colonic surgery was significantly lower (19.7% vs 51.5%, P < 0.01). Less than 10% prescribe oral antibiotic bowel preparation whereas 96% prescribe perioperative intravenous antibiotics. Conclusion: Among the majority of respondents to this survey, MBP is used routinely for rectal operations. For colonic surgery, laparoscopic surgeons have a significantly lower use of MBP. Use of oral antibiotic bowel preparation remains uncommon.